Readiness of Culinary Arts Students from the Aspect of Technical Skills to Employability at Muar Vocational College - Siti Hajar binti Zakariah,; Muhammad Idlan Danial, (Research and Innovation in Technical and Vocational Education and Training, 2024)
Graduate unemployment is still a major issue in Malaysia because employers prefer workers with technical skills only to academic abilities. The aim of this study is to determine the level of technical skill preparedness among students of Muar Vocational College, Johor. This study is quantitative with a survey approach. The population of this study was 85 Culinary Arts students and the sample size was 70 respondents who were selected for this study. This study uses a questionnaire form that has 30 items. The Statistical Package for Social Science Version 29 software is used to analyze the collected data. The results of this study found a high level of technical skills with a min rating of 4.43 and the level of employability of students at the Muar Vocational College was also high at a min score of 4.12. This shows respondents are skilled in handling equipment, have a good knowledge of the correct procedures and are ready to embark on the workplace. For the Conclusion, the objective of this study has been achieved. This study suggests for future studies, objectives can be developed such as finding differences between men and women from the readiness of human skills to employability.